Visual, Auditory, Kinesthetic Learning Styles In the perspective of the Qur'an - Juariah, Siti; Achmad, Yudianto; Edy, Sarwo (DPPM Universitas Pelita Bangsa, 2023)
Humans have different learning styles including: visual learning styles or based on vision; auditory learning style or based on hearing; and kinesthetic learning styles based on feelings. Learning styles in a scientific perspective already exist in the Qur'an, in Surah An-Nahl (16:78): learning style